PENGARUH METODE PEMBELAJARAN DIRECT INSTRUCTION MELALUI PENDEKATAN MEDIA VIDEO TERHADAP HASIL BELAJAR RENANG GAYA DADA - Hesty Yuliani Hadi; Irwan Hermawan; Asep Angga Permadi (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
Physical education is one of the subjects in schools, including junior high schools. Learning to swim is not easy, as is the case with class VII students at SMPN 1 Cikajang. Where they still have many difficulties in learning to swim, especially in breaststroke swimming. One of the learning methods that can be used in this case is the Direct Instruction Method (Direct Instruction/DI) with the Media Video approach. This study aims to determine the effect of increasing learning outcomes in breaststroke swimming material in class VII A students of SMPN 1 Cikajang. The direct learning model assisted by video media is very good for improving learning outcomes in breaststroke swimming for class VII A students of SMPN 1 Cikajang. From the results of the analysis obtained a significant increase from cycle I, cycle II and cycle III. The results of learning to swim breaststroke in cycle I in the Good category was 7.40%, the number of students who completed was 15 students. In cycle II there was an increase in the percentage of student learning outcomes in the Good category of 33.3%, while 23 students who completed. In cycle III, there was an increase in student learning outcomes in the good category of 48.1%, while 24 out of 27 students completed.